Luminescence in Electrochemistry : Applications in Analytical Chemistry, Physics and Biology - Miomandre, Fabien; Audebert, Pierre (Springer International Publishing : Imprint: Springer, 2017)
This book highlights the various topics in which luminescence and electrochemistry are intimately coupled. The topic of this book is clearly at the frontier between several scientific domains involving physics, chemistry and biology. Applications in these various fields naturally also need to be mentioned, especially concerning displays and advanced investigation techniques in analytical chemistry or for biomedical issues.
Keywords: Chemistry.; Spectroscopy.; Electrochemistry.; Microscopy.; elektronické knihy; electronic books